Exploring amygdala structural changes and signaling pathways in postmortem brains: consequences of long-term methamphetamine addiction - Azimzadeh, Zahra; Omidvari, Samareh; Niknazar, Somayeh; Vafaei-Nezhad, Saeed; Roozbahany, Navid Ahmady; Abdollahifar, Mohammad-Amin; Tahmasebinia, Foozhan; Mahmoudiasl, Gholam-Reza; Abbaszadeh, Hojjat Allah; Darabi, Shahram (Anatomy & cell biology, 2024)
Methamphetamine (METH) can potentially disrupt neurotransmitters activities in the central nervous system (CNS) and cause neurotoxicity through various pathways. These pathways include increased production of reactive nitrogen and oxygen species, hypothermia, and induction of mitochondrial apoptosis. In this study, we investigated the long-term effects of METH addiction on the structural changes in the amygdala of postmortem human brains and the involvement of the brain- cAMP response element-binding protein/brain-derived neurotrophic factor ( ) and signaling pathways. We examined ten male postmortem brains, comparing control subjects with chronic METH users, using immunohistochemistry, real-time polymerase chain reaction (to measure levels of , and tumor necrosis factor-α [ ]), Tunnel assay, stereology, and assays for reactive oxygen species (ROS), glutathione disulfide (GSSG), and glutathione peroxidase (GPX). The findings revealed that METH significantly reduced the expression of , and GPX while increasing the levels of GSSG, ROS, RIPK3, , and . Furthermore, METH-induced inflammation and neurodegeneration in the amygdala, with ROS production mediated by the and signaling pathways.